High-thermal-conductivity gasket and preparation method thereof

Through the molding technology of high-thermal conductivity gaskets prepared in a strong magnetic field environment, combined with matrix resin and thermal filler, the problem of insufficient thermal conductivity of existing thermal conductivity gaskets is solved, and efficient heat dissipation effect of electronic equipment is achieved.

CN119410155APending Publication Date: 2025-02-11SHENZHEN DARBOND INTERFACE MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737093.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing thermal conductivity gaskets have low thermal conductivity, high thermal resistance and poor heat transfer efficiency, which cannot meet the heat dissipation needs of high-performance electronic equipment.

Method used

High thermal conductivity gaskets prepared in a strong magnetic field environment, including matrix resin, crosslinking agent, catalyst, inhibitor, antioxidant and thermal filler, are used to form high thermal conductivity by vacuum stirring and extrusion of the material under the action of magnetic field. gaskets.

Benefits of technology

The thermal conductivity reaches 18w/m.k, which reduces the contact thermal resistance between interfaces, improves the heat dissipation efficiency of electronic equipment, and remains stable in a high-temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410155A_ABST
    Figure CN119410155A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat conduction materials, in particular to a high-heat-conduction gasket and a preparation method thereof. The high-thermal-conductivity gasket is prepared from the following components in parts by weight: 5 to 10 parts of matrix resin with the molecular weight of 500 to 2000, 0.1 to 1.0 part of a cross-linking agent, 0.1 to 0.5 part of a catalyst, 0.01 to 0.1 part of an inhibitor, 0.1 to 2 parts of an antioxidant and 50 to 90 parts of thermal-conductivity filler. The heat conductivity coefficient of the heat-conducting gasket reaches up to 18w / m.k, when the temperature exceeds 65 DEG C, the microcrystalline wax in the colloid is subjected to phase change, so that the wettability between interfaces is better, the contact thermal resistance between the interfaces is reduced, the overall thermal resistance of the heat-conducting gasket is greatly reduced, the preparation method is simple, and industrial production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, and in particular to a high thermal conductive gasket and a preparation method thereof. Background Art

[0002] As electronic devices become more high-performance and miniaturized, heat dissipation issues are becoming increasingly prominent. As an effective heat dissipation material, high thermal conductivity gaskets can absorb and transfer heat when electronic devices are working, thereby reducing device temperature and improving device stability and reliability.

[0003] The thermally conductive gaskets in the prior art have the problems of low thermal conductivity, high thermal resistance, poor heat transfer efficiency, etc., and cannot meet the heat dissipation requirements of high-performance electronic devices. Summary of the invention

[0004] In view of the above deficiencies in the prior art, an object of the present invention is to provide a high thermal conductivity gasket and a preparation method thereof.

[0005] To achieve the above objectives, the technical solutions adopted are:

[0006] One of the purposes of the present invention is to provide a high thermal conductivity gasket, comprising the following components in parts by weight: 5-10 parts of a base resin with a molecular weight of 500 to 2000, 0.1-1.0 parts of a cross-linking agent, 0.1-0.5 parts of a catalyst, 0.01-0.1 parts of an inhibitor, 0.1-2 parts of an antioxidant, and 50-90 parts of a thermal conductive filler; the thermal conductive filler comprises the following components in parts by weight: 5-20 parts of spherical aluminum nitride with a particle size of 0.6-50um; microcrystalline wax graphite whiskers with a diameter of 0.5-6um and a length of 100um-1mm, 20-80 parts of spiral columns, microcrystalline wax covering 50% of the surface area of ​​the outer surface of the graphite whiskers, and 5-30 parts of diamond micropowder with a particle size of 30-150um.

[0007] Furthermore, the base resin is a vinyl siloxane with a molecular weight of 500-2000, a viscosity of 200-1000 cps, and a vinyl content of 0.10-0.25 mmol / g, and the crosslinking agent is a double hydrogen-terminated siloxane with a molecular weight of 350-1500, a viscosity of 200-1000 cps, and a hydrogen content (molar content) of 0.18%-1.36%.

[0008] Furthermore, the catalyst is a platinum-chloroplatinic acid complex with a platinum content of 2000 PPM.

[0009] Furthermore, the inhibitor is alkynyl cyclohexanol with a concentration of 0.5%.

[0010] Furthermore, the phase transition point of the microcrystalline wax is 65°C.

[0011] Furthermore, the antioxidant is 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate.

[0012] The second object of the present invention is to provide a method for preparing the high thermal conductivity gasket, comprising the following steps: a: mixing the base material, adding the base resin, cross-linking agent, inhibitor, antioxidant, catalyst, and thermal conductive filler into a vacuum mixer and mixing them evenly, with a stirring speed of 15-20RPM and a vacuum degree of -0.09MPa, and the evenly mixed material is ready for use; b: molding, pressurizing the above-mentioned evenly mixed material through a screw machine, transporting it through a pipeline, and finally discharging the glue through a slit cavity glue nozzle made of nickel-iron alloy, the glue nozzle specification is a rectangular slit shape with a length of 200mm and a width of 3mm, and the entire glue coating platform is in In a magnetic field with a magnetic field strength of 1T, the electromagnet is composed of two plate-shaped electromagnets. When the material is physically compressed, extruded and coated through the nozzle, under the action of the magnetic field, the filler will automatically arrange in the same direction, and after extrusion, a long strip of rubber is formed, and then multiple strips are stacked together to form a rectangular block with a certain thickness. Finally, the rectangular block is placed in a tunnel furnace at 125°C for curing for 60-90 minutes until the hardness inside and outside is consistent, forming a primary gasket matrix; c: Slicing, the primary gasket matrix is ​​cut into sheets of standard thickness by an ultrasonic cutting knife, and the cutting direction is perpendicular to the nozzle extrusion coating direction.

[0013] The beneficial effect of adopting the above technical solution is that the magnetic field strength is 1T. If the magnetic field strength is too small, it will have little effect, and if it is too strong, it will affect the arrangement of powder particles.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The present invention extrude the material from a flat-mouth glue outlet through compression in a strong magnetic field environment to form a rectangular rubber strip. The material passes through a slit under the action of an external force, and fillers inside the rubber material are arranged in a certain direction. Because the fillers have the same direction, the thermal conductivity can reach 18w / mk. When the temperature exceeds 65°C, the microcrystalline wax inside the colloid undergoes a phase change, and can absorb heat in time at high temperatures and remain stable in a low-temperature environment, thereby ensuring the stable operation of electronic equipment, allowing better wettability between interfaces, reducing the contact thermal resistance between interfaces, and greatly reducing the overall thermal resistance of the thermally conductive gasket, which can effectively improve the heat dissipation efficiency of electronic equipment. The preparation method is simple and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a structural schematic diagram of the glue dispensing nozzle of the present invention;

[0017] Figure 2 This is a schematic diagram of glue coating on a magnetic field coating platform according to the present invention. DETAILED DESCRIPTION

[0018] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0019] Example 1

[0020] A high thermal conductivity gasket, the preparation steps and methods are as follows: a. base material mixing, 8 parts of vinyl silicone oil with a viscosity of 1000cps, a molecular weight of 2000, and a vinyl content of 0.11mmol / g, 0.3 parts of hydrogenated silicone oil with a viscosity of 200cps, a molecular weight of 350, and a silicon hydrogen content of 1.36%, 0.06 parts of alkynyl cyclohexanol with a content of 0.5%, 0.5 parts of 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate as an antioxidant, 0.14 parts of chloroplatinic acid platinum complex with a platinum content of 2000PPM as a catalyst, and 10 um spherical aluminum nitride powder 13 parts, diameter 5um, length 0.6mm, microcrystalline wax graphite whisker powder wrapped with 50% microcrystalline wax 53 parts, particle size 125um diamond powder 25 parts, the above materials are added to a vacuum mixer, set the stirring speed 15RPM stirring for 10 minutes, clean the stirring paddle, increase the speed to 20RPM, set the vacuum degree -0.09MPa, vacuum stirring for 30 minutes, the stirred material is ready for use; b: molding, the above mixed material is put into a screw machine, the pressure is set to 0.6MPa, the material is transported through a pipeline, and finally the glue is discharged from the slit cavity glue nozzle made of nickel-iron alloy, such as Figure 1 As shown, the glue nozzle is a rectangular slit with a length of 200 mm and a width of 3 mm. Figure 2 As shown, the electromagnet is turned on at the same time, and the magnetic field strength is set to 1T. Figure 2 The dotted arrow in the middle represents the direction of the magnetic field. During the entire gluing process, the glue nozzle is in the middle of the electromagnetic field, and the glue nozzle gradually moves backward perpendicular to the direction of the magnetic field. The glue is coated on the surface of the release film to form a long strip of glue. Under the action of the magnetic field and physical compression, the filler will automatically arrange in the same direction. After repeated gluing, multiple glue strips are stacked together to form a rectangular block with a certain thickness. The rectangular block is then placed in a tunnel oven at 125°C for curing for 60-90 minutes until the hardness inside and outside is consistent, forming a primary gasket matrix; c: Slicing, fix the primary gasket matrix, and use an ultrasonic cutter to cut it into 1-3mm sheets. The cutting direction is perpendicular to the nozzle extrusion coating direction.

[0021] Example 2

[0022] A high thermal conductivity gasket, the preparation steps and methods are as follows: a. base material mixing, selected viscosity 500cps, molecular weight 1000, vinyl content 0.18mmol / g vinyl silicone oil 8 parts, viscosity 200cps, molecular weight 350, 1.36% of hydrogenated silicone oil 0.3 parts, inhibitor selected content 0.5% alkynyl cyclohexanol 0.06 parts, antioxidant selected 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate 0. 5 parts, 0.14 parts of platinum chloroplatinate complex with a platinum content of 2000PPM as a catalyst, 5 parts of spherical aluminum nitride powder with a particle size of 5um, 3um in diameter and 1mm in length as a thermal conductive filler, 70 parts of microcrystalline wax graphite whisker powder wrapped with 50% microcrystalline wax, and 16 parts of diamond micropowder with a particle size of 150um. Add the above materials to a vacuum mixer respectively, set the stirring speed to 15RPM and stir for 10 minutes. After cleaning the stirring paddle, increase the speed to 20RPM and set the vacuum degree to -0.09M Pa, vacuum stirring for 30 minutes, and the uniformly stirred material is ready for use; b: molding, the above-mentioned uniformly mixed material is put into a screw machine, the pressure is set to 0.6MPa, the material is transported through a pipeline, and finally the glue is discharged from the slit cavity nozzle made of nickel-iron alloy. The glue nozzle specification is a rectangular slit with a length of 200mm and a width of 3mm. At the same time, the electromagnet is turned on, and the magnetic field strength is set to 1T. During the entire gluing process, the glue nozzle is in the middle of the electromagnetic field, and the glue nozzle gradually moves backward perpendicular to the direction of the magnetic field. The glue is coated on the surface of the release film to form a long strip of glue. Under the action of the magnetic field and physical compression, the filler will automatically arrange in the same direction. After repeated gluing, multiple glue strips are stacked together to form a rectangular block with a certain thickness. Then the rectangular block is placed in a tunnel furnace at 125°C for curing for 60-90 minutes until the hardness inside and outside is consistent to form a primary gasket matrix; c: slicing, fix the primary gasket matrix, and use an ultrasonic cutting knife to cut it into 1-3mm sheets, and the cutting direction is perpendicular to the extrusion coating direction of the glue nozzle.

[0023] Example 3

[0024] A high thermal conductivity gasket, the preparation steps and methods are as follows: a. base material mixing, selected viscosity 200cps, molecular weight 500, vinyl content 0.25mmol / g vinyl silicone oil 8 parts, viscosity 200cps, molecular weight 350, 1.36% of hydrogenated silicone oil 0.3 parts, inhibitor selected content 0.5% alkynyl cyclohexanol 0.06 parts, antioxidant selected 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate 0.5 parts 1. The catalyst is 0.14 parts of platinum chloroplatinate complex with a platinum content of 2000PPM, 15 parts of spherical aluminum nitride powder with a particle size of 50um, a diameter of 3um, and a length of 1mm for thermal conductive filler, 50 parts of microcrystalline wax graphite whisker powder wrapped with 50% microcrystalline wax, and 26 parts of diamond micropowder with a particle size of 45um. The above materials are added to a vacuum mixer respectively, and the stirring speed is set to 15RPM and stirred for 10 minutes. After cleaning the stirring paddle, the speed is increased to 20RPM and the vacuum degree is set to -0.09M. Pa, vacuum stirring for 30 minutes, and the uniformly stirred material is ready for use; b: molding, the above-mentioned uniformly mixed material is put into a screw machine, the pressure is set to 0.6MPa, the material is transported through a pipeline, and finally the glue is discharged from the slit cavity nozzle made of nickel-iron alloy. The glue nozzle specification is a rectangular slit with a length of 200mm and a width of 3mm. At the same time, the electromagnet is turned on, and the magnetic field strength is set to 1T. During the entire gluing process, the glue nozzle is in the middle of the electromagnetic field, and the glue nozzle gradually moves backward perpendicular to the direction of the magnetic field. The glue is coated on the surface of the release film to form a long strip of glue. Under the action of the magnetic field and physical compression, the filler will automatically arrange in the same direction. After repeated gluing, multiple glue strips are stacked together to form a rectangular block with a certain thickness. Then the rectangular block is placed in a tunnel furnace at 125°C for curing for 60-90 minutes until the hardness inside and outside is consistent to form a primary gasket matrix; c: slicing, fix the primary gasket matrix, and use an ultrasonic cutting knife to cut it into 1-3mm sheets, and the cutting direction is perpendicular to the extrusion coating direction of the glue nozzle.

[0025] The cut gaskets of Examples 1-3 were tested for relevant indicators, as shown in Table 1. From the data in the table, it can be seen that the thermally conductive gaskets prepared in Examples 1-3 have high thermal conductivity, good thermal stability and mechanical properties.

[0026] Table 1. Thermal insulation sheet performance test of Examples 1-3

[0027]

[0028]

[0029] It can be seen from the experimental comparison data that under low pressure, the thermal conductivity of all gaskets is relatively high. When the pressure increases, the thermal conductivity decreases significantly. This is because, under low pressure test conditions, the thermal conductivity has obvious advantages in the trend direction. When the pressure increases, the thermally conductive gasket is compressed more severely, and the thermally conductive filler inside the gasket is no longer arranged in a trend, affecting the overall thermal conductivity of the gasket. Therefore, it can be judged that the above method can indeed prepare products with a certain trend, and the thermal conductivity is significantly improved in the trend direction of the filler; thermal resistance test data, when the test is 10psi, 50℃, the test thermal resistance value does not change significantly, when the test conditions are 10psi, 80℃, the thermal resistance is significantly reduced. The reason is that when the temperature exceeds 65℃, a phase change occurs in the component, the wettability at the interface is improved, and the overall thermal resistance is significantly reduced.

[0030] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity gasket, characterized in that: The invention comprises the following components in parts by weight: 5-10 parts of a base resin with a molecular weight of 500 to 2000, 0.1-1.0 parts of a cross-linking agent, 0.1-0.5 parts of a catalyst, 0.01-0.1 parts of an inhibitor, 0.1-2 parts of an antioxidant, and 50-90 parts of a thermally conductive filler; the thermally conductive filler comprises the following components in parts by weight: 5-20 parts of spherical aluminum nitride with a particle size of 0.6-50um; microcrystalline wax graphite whiskers with a diameter of 0.5-6um and a length of 100um-1mm, 20-80 parts of spiral columns, microcrystalline wax covering 50% of the surface area of ​​the outer surface of the graphite whiskers, and 5-30 parts of diamond micropowder with a particle size of 30-150um.

2. The high thermal conductivity gasket according to claim 1, characterized in that: The base resin is vinyl siloxane with a molecular weight of 500-2000, a viscosity of 200-1000 cps and a vinyl content of 0.10-0.25 mmol / g. The crosslinking agent is a double hydrogen-terminated siloxane with a molecular weight of 350-1500, a viscosity of 200-1000 cps and a hydrogen content of 0.18%-1.36%.

3. The high thermal conductivity gasket according to claim 1, characterized in that: The catalyst is a chloroplatinic acid platinum complex with a platinum content of 2000 PPM.

4. The high thermal conductivity gasket according to claim 1, characterized in that: The inhibitor is alkynyl cyclohexanol at a concentration of 0.5%.

5. The high thermal conductivity gasket according to claim 1, characterized in that: The phase transition point of the microcrystalline wax is 65°C.

6. The high thermal conductivity gasket according to claim 1, characterized in that: The antioxidant is 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate.

7. A method for preparing a high thermal conductivity gasket according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: a: mixing the base material, adding the base resin, the cross-linking agent, the inhibitor, the antioxidant, the catalyst and the thermal conductive filler into a vacuum mixer and mixing them evenly, with a stirring speed of 15-20RPM and a vacuum degree of -0.09MPa, and the evenly mixed material is set aside; b: molding, pressurizing the evenly mixed material through a screw machine, transporting it through a pipeline, and finally discharging the glue through a slit cavity glue nozzle made of nickel-iron alloy, the entire glue coating platform is in a magnetic field with a magnetic field strength of 1T, the electromagnet is composed of two plate-shaped electromagnets, when the material is physically compressed and extruded through the glue nozzle, under the action of the magnetic field, the filler will automatically arrange in the same direction, and a long strip of glue will be formed after extrusion, and then a plurality of glue strips will be stacked together to form a rectangular parallelepiped, and finally the rectangular parallelepiped will be placed in a tunnel furnace at 125°C for curing for 60-90 minutes until the hardness inside and outside is consistent, so as to form a primary gasket matrix; c: Slicing: Cut the primary gasket matrix into sheets of standard thickness using an ultrasonic cutter.